KONTRIBUSI PENDAPATAN MASYARAKAT DARI SISTEM AGROFORESTRI DI KHDTK UNLAM - Syamsudin Syamsudin; Mahrus Aryadi; Eva Prihatiningtyas (Universitas Lambung Mangkurat, 2020)
The Contribution Revenue From The Agroforestry System of The Community: A Case Study In KHDTK Village Of West Mandiangin UNLAM Banjar South Kalimantan. This research was conducted by means of purposive sampling (specified in advance) and interviews (open ended interview) uses structured questions in the population who manage land by agroforestry. The number of respondents that was taken were 5 informants who manage land with agroforestry system. The results note that the most widely cultivated plants are rubber plantations, the yellow-fruit (langsat), durian and jackfruit (cempedak) with highest revenues amounted to Rp21.603 million from the agroforestry management for one year. While the lowest income amounted to Rp9.618 million. The crop harvested after 10 years. The highest contributes to 94% of net management effort cost, and the agroforestry Contribution to other results as well as contribute to the income of the most agroforestri efforts outside high 77%. The results of this research is known that the type of plant that produces the most high revenue is rubber tree from the rubber resin (gatah) sale proceeds to resin, due to the type of plant that can be harvested every day, with the sale for one year weighted 1,455 kg with a selling price up to Rp6.600/kg and the least is durian plant which only produce 450 kg/harvest season with sale price is up to Rp10.000/kg.Keywords: contribution; revenue; community; agroforestry